Model dan Modul Edukasi ‘Financial English’ untuk Meningkatkan Literasi Keuangan dan Investasi Gen-Z di Kabupaten Tolitoli - Yunus H, Ismail; Marlina; Widodo, Julistyono (LPPM Universitas Madako Tolitoli, 2025)
Financial literacy and investment awareness are essential competencies for young people in the digital economy era. However, students of Generation Z in regional areas such as Tolitoli Regency continue to face significant gaps in understanding basic financial concepts and common investment terms—especially when such information is presented in English. This study aims to: (1) identify the current state of financial and investment literacy, along with English comprehension related to financial contexts among Gen-Z students in Tolitoli; (2) develop an educational model and module of Financial English tailored to local needs; and (3) evaluate the effectiveness of the module in enhancing financial understanding and decision-making skills. The research employed a research and development approach, combining surveys, interviews, pre- and post-tests, and expert validation as data collection methods. Findings revealed low levels of investment literacy and limited comprehension of financial English terminology, with language acting as a major barrier to accessing credible financial information. The developed module, which integrates localized financial education with contextual English learning, proved effective in improving both conceptual understanding and students’ confidence in managing financial decisions. These results suggest that a contextual, dual-focus approach can serve as a strategic solution for strengthening the financial preparedness of young people in underserved regions.